Simultaneous laparoscopic repair of intestinal malrotation and ileal duplication - Go Miyano; Hiromu Miyake; Masakatsu Kaneshiro; Mariko Koyama; Keiichi Morita; Masaya Yamoto; Hiroshi Nouso; Koji Fukumoto; Naoto Urushihara (Elsevier, 2018)
An 8-year old boy was referred for chronic, frequent bilious vomiting and intermittent abdominal pain. Intestinal malrotation was diagnosed by upper gastrointestinal study (UGI) and laparoscopic Ladd's procedure was performed. Ladd's bands were laparoscopically dissected out, and the mesentery was dissected to be broaden. After performing Ladd's procedure, an ileal duplication cyst was found 30 cm proximal to the terminal ileum, which was extracted through the umbilical port site and was totally resected. Three years postoperatively, the patient has had no further symptoms. Keywords: Laparoscopy, Malrotation, Duplication